PENGARUH PERLAKUAN PWHT PADA BAJA ASTM A36 TERHADAP KEKUATAN TARIK - I Wayan Ekagra Mana Krsna Gita; Djarot B. Darmadi; Sugiarto (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Welding has an important role in the industrial world. To improve the material properties of welded joints, several treatments are carried out after the welding process. This study aims to determine the tensile strength value of ASTM A36 material welding joints that have gone through the post weld heat treatment (PWHT) process. The real experimental method is applied in this research. The welding used in this research is GTAW. The GTAW welding process uses a current of 80 A. While the PWHT process uses a temperature variable of 500°C. Data analysis of tensile test results using quantitative descriptive methods. The test results and data analysis obtained show that: (1) Raw material has a tensile strength of 429 MPa, this value is the highest among the GTAW welding variables with PWHT and without PWHT). (2) PWHT temperature has a significant effect on strain. (3) The welding process with a current of 80 A followed by a PWHT process on ASTM A36 steel material is the one that has a strain value close to the raw material, which is 9.26%.